(untitled) (Damascus University Journal for the economic and Political sciences, 2026)
This study aimed to know the role of public relations in improving hotel performance at Dama Rose Hotel in the city of Damascus. Within the framework of addressing the research problem represented by: “Role of public relations in improving hotel performance at the Dama Rose Hotel, affiliated with the Ministry of Tourism in the city of Damascus, among its internal audience.” In addition, whether had the public relations programs adopted by Dama Rose Hotel, affiliated with the Ministry of Tourism in Damascus, currently sufficient to improve performance We touched on the theoretical aspect of the concept of public relations, the mechanisms of its work and its importance in hotels, and an overview of the development of public relations, which had considered as old as man is and had considered the foundation in hotels. We also touched on the concept of hotel performance, its concept and importance. The researcher used the descriptive analytical method، through the survey tool (questionnaire) with a simple random sample of workers in the hotel, where 50 questionnaires were distributed, and the use of statistical analysis software to analyze the data، as the study showed some important results. Such as: 1- The public relations programs adopted by Dama Rose Hotel had considered insufficient to improve performance and need more programs. 2- There is an impact of internal public relations on hotel performance at Dama Rose Hotel. In light of the previous results, it had concluded that it is necessary to pay attention to public relations and to use public relations programs that contribute to improving performance at Dama Rose Hotel in Damascus.